Tiyazol grupları içeren ftalosiyaninler - Zengin Uzunmehmetoğlu, Hilal (Fen Bilimleri Enstitüsü, 2019)
Ftalosiyaninler, konjuge 18 -elektronu bulunan makrosiklik bileşik sınıfıdır. Kimyasal stabilite ve termal kararlılık gösteren ftalosiyaninler ayrıca çoklu ve reversibil elektron transfer özelliklerine sahiptirler. Periyodik tablodaki birçok farklı element merkez atom olarak kullanılmıştır. Ayrıca aromatik elektrofilik ve nükleofilik yer değiştirme reaksiyonlarından faydalanılarak farklı ftalosiyanin türevlerinin hazırlanabileceği görülmektedir. Ftalosiyaninler yüksek parlaklık ve yüksek termal özellikleri, kimyasal stabiliteleri, geliştirilebilir spektroskopik özelliklerinden dolayı birçok farklı uygulama alanına sahiptir. Fotodinamik terapide (PDT) fotohassaslaştırıcı olarak, kimyasal sensörler, elektrokromik görüntüleme cihazları, sıvı kristaller, yarı iletkenler, doğrusal olmayan optikler ve elektrokromik görüntüleme cihazları gibi çeşitli teknolojik uygulamalarda kullanılmaktadır. Tiyazoller, farmakolojik ve biyolojik özellikleri sayesinde, önemli bir heterosiklik bileşik sınıfıdır; anti-kanser, antikonvülsan, anti-parkinson, antiviral ve antidiyabetik gibi birçok farklı uygulamada kullanılır. Biyolojik kullanımlarına ek olarak, tiyazol türevleri elektrokimyada alanında da çalışılmaktadır. Bu çalışmada da fenil tiyazol grubu içeren yeni tip ftalosiyanin türevlerinin sentezi, spektrokimyasal ve elektrokimyasal karakterizasyonu hedeflenmiştir. Çalışmanın ilk kısmında, 4-nitro-ftalonitril ve 4-feniltiyazol-2-tiol ile nükleofilik aromatik sübstitüsyon reaksiyonu sonucu 4-(4-fenil-2-tiyazolil)tiyoftalonitril (1) bileşiği sentezlenmiştir. Elde edilen ftalonitrilin (1) Zn(CH3COO)2, CoCl2 ve MnCl2 metal tuzları ile DMAE varlığında reaksiyonu gerçekleştirilerek hedeflenen CoPc1a, ZnPc1b, ve Mn(Cl)Pc1c elde edilmiştir. Ftalonitrilin (1) FT-IR spektrumunda, başlangıç maddesi olan dinitril türevine ait 1350 cm-1'de bulunan NO2 bandının kaybolması ve 2233 cm-1'de -C≡N gruplarının gerilme titreşimlerin oluşması hedeflenen yapının oluştuğunu doğrulamaktadır. Bileşiğin CDCl3 içerisinde ölçülen 1H-NMR spektrumu sonuçlarında ftalonitril grubundaki aromatik C-H protonlar δ7,85, 7,78-7,73 ppm'de, tiyazol grubuna ait aromatik proton 7,69'da, fenil grubuna ait protonlar ise 7,91-7,90, 7,49-7,46, 7,42-7,39 ppm'de gözlemlenmiştir. Periferal tetra sübstitüe CoPc1a, ZnPc1b, ve Mn(Cl)Pc1c bileşiklerinin IR spektrumunda, 3061-3094 cm-1 arasında aromatik C-H gerilme bantlarına ait titreşimler görülmüştür. ZnPc1b'nin 1H-NMR spektrumunda aromatik protonlar δ9,21-9,03 (4H), 9,93-8,71 (4H), 8,41-8,27 (4H), 8,20-8,07 (12H) ve 7,44-7,29 (12H) ppm'de gözlemlenmiştir. MALDI-TOF tekniği ile alınan kütle spektroskopisinde CoPc1a ve Mn(Cl)Pc1c yapılarına ait 1337,70'deki [M+1]+ ve 1369,31'deki [M+1]+ görülen pikler ftalosiyanininlerin oluştuğunu kanıtlamaktadır. Ayrıca CoPc1a ve ZnPc1b ftalosiyaninlerin THF içerisinde UV-vis spektrumunda B ve Q bantları sırasıyla 331, 348 nm ve 666, 680 nm'de gözlemlenmiştir. Mn(Cl)Pc1c bileşiğinin DCM içerisindeki UV-vis spektrumunda ise 321 ve 735 nm'de absorbsiyon bandları görülmektedir. CoPc1a ve ZnPc1b ftalosiyaninlerinin THF içerisindeki agregasyon davranışları da araştırılmış olup 2-14×10-6 M derişim aralığında agregasyon göstermediği ve Beer-Lambert yasasına uyum sağladığı görülmüştür. Çalışmanın ikinci kısmında non-periferal ftalonitril türevi olan 3-(4-fenil-2-tiyazolil)tiyoftalonitril 2; 3-nitro ftalonitrilin 4-feniltiyazol-2-tiol ile susuz K2CO3 varlığında nükleofilik yer değiştirme reaksiyonu sonucu sentezlenmiştir. Non periferal metalli ftalosiyaninler (CoPc2a, ZnPc2b, Mn(Cl)Pc2c), 2 bileşiğinin CoCl2, Zn(CH3COO)2 ve MnCl2 metal tuzları ile siklotetramerizasyonu sonucunda elde edilmiştir. Bileşiğin (2) FT-IR spektrumunda, -C≡N gruplarına ait gerilme titreşimleri 2235 cm-1 görülmesi yapının oluşumunu desteklemektedir. 2 bileşiğinin DMSO-d6 içerisinde ölçülen 1H-NMR spektrumunda fenil grubuna ait protonlar 7,89-7,90 (d), 7,43-7,46 (t), 7,35-7,38 (d) olarak, tiyazol grubuna ait aromatik proton ise 8.28 da singlet olarak, dinitril grubuna ait aromatik C-H protonlar ise 8,20-8,21 (d), 8,08-8,09 (d), 7,94-7,97 (t) ppm'de yapıyı destekleyecek şekilde gözlemlenmiştir. Kütle spektrumunda bileşiğin moleküler iyon piki m/z=319'da görülmüştür. ZnPc2b bileşiğinin DMSO-d6 içerisinde ölçülen 1H-NMR spektrumu sonucuna göre aromatik protonlar 9,03-8,87 (4H), 8,23-7,81 (20H), 7,49-7,46 (4H) ve 7,37-7,28 (8H) ppm'de gözlemlenmiştir. CoPc2a bileşiğinin moleküler iyon piki 1337,55 [M+1]+, Mn(Cl)Pc2c bileşiğinin ise 1331,38 [M-Cl+1]+ olarak gözlemlenmiştir. CoPc2a ve ZnPc2b ftalosiyaninlerinin THF'te alınan UV-vis spetktrumlarında sırasıyla Q bantları 678, 695 nm'de, B bantları 328, 336 nm'de görülmüştür. Mn(Cl)Pc2c'nin THF içerisindeki UV-vis spektrumunda ise 317 ve 629 nm'de absorbsiyon bandları görülmektedir. Çalışmanın üçüncü kısmında okta-sübstitüe ftalosiyaninlerin başlangıç maddesi olarak seçilen 4,5-(4-fenil-2-tiyazolil)tiyoftalonitril 3, 4,5 dikloroftalonitril ve 4-feniltiyazol-2-tiolün reaksiyonundan elde edilmiştir. Reaksiyon sonucu elde edilen 4,5-(4-fenil-2-tiyazolil)tiyo-ftalonitrilden 3, 2-(dimetilamino)etanol ortamında Zn(CH3COO)2 ve MnCl2 metal tuzları varlığında ftalosiyanin türevlerine geçilmiştir. 3 bileşiğinin IR spektrumunda -C≡N grununun gerilme titreşimleri 2230 cm-1'de, aromatik C-H gruplarının gerilme titreşimleri 3104 cm-1'de gözlemlenmiştir. 3 bileşiğinin DMSO-d6 içerisinde ölçülen 1HNMR spektrumu sonucuna göre fenil protanları 7,94-7,92 (4H), 7,47-7,44 (4H), 7,39-7,36 (2H) ppm'de çıkmıştır. Tiyazol halkasına ait protonlar 8,30 ppm'de görülürken ftalonitril kısmındaki protonlar 8,35 ppm'de gözlenmiştir. ZnPc3a 1H-NMR spektrumuna göre aromatik protonların pikleri 8,31-7,36 ppm arasında gözlemlenmektedir. Mn(Cl)Pc3b kütle spektrumundaki 2096,40 [M-Cl+1]+ yapının oluştuğunu desteklemektedir. THF içerisinde ölçülen UV-Vis spektrumunda, ZnPc3a'nın B bandı 363 nm ve Q bandı 703 nm'de gözlemlenirken PMn(Cl)Pc3b'nin absorpsiyon bantları sırasıyla 330 ve 655 nm'de gözlemlenmektedir. Sentezlenen ftalosiyaninlerin türevlerinin elektrokimyasal ve spektroelektroelektrokimyasal özellikleri incelenmiştir. Periferal sübstitue tiyazol grubu içeren komplekslerin elektrokimyasal ve spektroelektrokimyasal sonuçları, CoPc1a ve Mn(Cl)Pc1c yapıların Co(II) ve Mn (III) metal merkezlerinin, Pc bazlı elektron transfer reaksiyonlarına ek olarak ekstra metal bazlı redoks işlemler verdiğini göstermiştir. Ayrıca periferal tiyazol grubu içeren ftalosiyaninlerden elektropolimerizasyonla iletken redoks aktif modifiye elektrotlar hazırlanmış ve modifiye elektrotlarla suyun elektroliz reaksiyonu incelenmiş olup MnPc-bazlı (Mn(Cl)Pc1c) modifiye elektrotun suyun elektrolizi sırasında oksijen oluşumunu katalizlediği ve OER için oldukça yüksek elektrokatalitik aktivite gösterdiği tespit edilmiştir. Non periferal sübstitüe tiyazol grubu içeren komplekslerin elektrokimyasal ve spektroelektrokimyasal sonuçlarına bakıldığında ise özellikle CoPc2a ve Mn(Cl)Pc2c merkezi metallerin elektron transfer reaksiyonları nedeniyle zengin redoks özelliklerine sahip olduğu görülmüştür.

Phthalocyanines are a class of macrocyclic compounds having conjugated 18- π electrons and four isoindole units. The central cavity of phthalocyanines is suitable of accommodating most of metal ions of periodic table, in this way it can be possible to modify spectroscopic properties. In addition, it can be seen that aromatic substitution reactions which can be easily carried out in aromatic compounds can be adapted to phthalocyanines and that a large number of different phthalocyanine derivatives can be prepared by this method. Phthalocyanines with high chemical and thermal stability are extremely valuable because of their unique physical and chemical properties. The phthalocyanines in various structures offer an opportunity to expand their application areas such as electrophotography, optical data storage, electrochromic imaging devices, gas sensor, liquid crystal, use as a colorant for laser technology. The solubility of phthalocyanine derivatives has an important role for using phthalocyanines in many technological applications. To increase the solubility of phthalocyanines, studies are carried out to synthesize phthalocyanine derivatives which contain various substituents in peripheral / non-peripheral positions. Thiazole, an important aromatic heterocycle compunds contains both nitrogen and sulfur in the five membered ring. They, as a result of high solubility properties in many organic solvents and their pharmacological properties, are used in various biological applications as well as liquid crystals, fluorescent dyes, photonucleases and insecticides. Besides their biological applications, its derivatives are generally investigated in electrochemistry. In this study, synthesis, spectrochemical and electrochemical characterization of new types of phthalocyanine derivatives containing phenyl thiazole group was aimed. The first step in this study involves synthesis 4-(4-phenylthiazole-2-thio)- phthalonitrile (1) and the corresponding metallophthalocyanines. The synthesis of the 4-(4-phenythiazole-2-thio) phthalonitrile was obtained in 82% yield with the help of aromatic displacement reaction of 4-nitrophthalonitrile with 4-phenylthiazole-2-thiol. Also K2CO3 was used as the base for this nucleophilic aromatic displacement in dry DMF. Cyclotetramerization of 1 with anhydrous metal salts (CoCl2, Zn(CH3COO)2 and MnCl2) at 145 °C in 2-Dimethylaminoethanol enables to the formation of metallophthalocyanines (CoPc1a, ZnPc1b, Mn(Cl)Pc1c). In the FT-IR spectrum of the 4-(4-phenylthiazole-2-thio)-phthalonitrile (1), the disappearance of NO2 at 1350 cm-1 and the presence of -C≡N at 2233 cm-1 proved the formation of 1. In the 1H NMR spectrum of compound 1, the aromatic C-H signals of the dinitrile were observed at δ 7.85, 7.78–7.73 as a singlet (1H) and a multiplet (2H). The aromatic proton of thiazole was appeared at d = 7.69 ppm as a singlet. The aromatic protons which belong to the phenyl moiety were at δ7.91–7.90, 7.49-7.46, 7.49– 7.46. Formation of the CoPc1a, ZnPc1b and Mn(Cl)Pc1c was verified by the disappearance of the -C≡N peaks in the FTIR spectrum. Also their FTIR spectrums are similar to each other due to the low influence of metal ions on the bond vibrations, aromatic C-H and –C=C- vibrations were observed about 3061–3094 and 1474–72 cm-1. In the 1H NMR spectrum of ZnPc1b, the aromatic protons exhibited at δ 9.21– 9.03 (4H), 9.93–8.71 (4H), 8.41–8.27 (4H), 8.20–8.07 (12H) and 7.44–7.29 (12H) ppm. Additionally, the MALDI-TOF mass spectra showed the molecular peaks at m/z 1337.70 [M+1]+ for CoPc1a and 1369.31 [M+1]+ for Mn(Cl)Pc1c. Two characteristic strong absorption bands in UV–Vis spectrum enables to identify the structure of phthalocyanines. The UV–Vis spectra of CoPc1a, ZnPc1b showed characteristic intense single Q bands at 666 and 680 nm and Soret or B bands occured around 331 and 348 nm, in THF respectively. The electronic absorption spectra of Mn(Cl)Pc1c showed at 321 and 735 in DCM. In this study, the aggregation behaviour of the complexes Pcs 1a,1b was investigated in THF. They (1a,1b) did not show any aggregation in THF solution. The Beer–Lambert law was obeyed for all of these compounds in THF for the concentrations between 2.00 x10-6 -14.00 x 10-6 M. In the second part of the study 3-(4-phenythiazole-2-thio)phthalonitrile (2) was obtained as a result of reaction 3-nitrophthalonitrile and 4-phenylthiazole-2-thiol in DMF using K2CO3 as the base for this nucleophilic aromatic displacement. Cyclotetramerization of 2 with anhydrous metal salts (CoCl2, Zn(CH3COO)2 and MnCl2) at 145 °C in 2-Dimethylaminoethanol led to the formation of metallophthalocyanines (CoPc2a, ZnPc2b and Mn(Cl)Pc2c) The new vibration appeared at 2235 cm-1 (-C≡N) verified the formation of phthalonitrile (2) according to FT-IR spectral data. In the 1H-NMR spectrum of compound 2, the aromatic protons at phenyl ring appear at 7.89-7.90 (d), 7.43-7.46 (t), 7.35-7.38 (d). Also thiazole proton for this compound was observed at 8.28 (s). The protons at dinitrile appear at 8.20-8.21 (d), 8.08-8.09 (d), 7.94-7.97 (t) ppm. The MALDI-TOF mass spectra showed the molecular peaks at m/z 1337.5 [M+1]+ for CoPc2a and 1331.38 [M-Cl+1]+ for Mn(Cl)Pc2c. In the 1HNMR spectrum of ZnPc2b, aromatic protons appeared at 9.03-8.87 (4H), 8.23-7.81 (20H), 7.49-7.46 (4H), and 7.37-7.28 (8H) ppm. UV-Vis spectra of CoPc2a, and ZnPc2b showed intense single Q band absorption of the π→π* transitions at 678 and 695 nm and B bands of these phthalocyanines appeared at 328 and 336 nm respectively. In the UV-Vis spectra, absorption peaks of Mn(Cl)Pc2c were observed at 317 and 629 nm. In the last part of the study, 4,5-(4-phenythiazole-2-thio)phthalonitrile (3) was prepared by nucleophilic aromatic chloro displacement reaction of 4-phenylthiazole-2-thiol. Then octa substituted metallo phthalocyanines were synthesized from 4,5 dichlorophthalonitrile derivative (3) by using appropriate metal salts (Zn(CH3COO)2, MnCl2). According to FT-IR spectral data, the new vibration appeared at 2230 cm-1 (C≡N) verified the formation of phthalonitrile (3). In 3`s 1H-NMR spectrum, aromatic protons at 7,94-7,92 (4H), 7,47-7,44 (4H), 7,39-7,36 (2H) ppm and thiazole proton at 8.30 ppm were shown. Aromatic protons of ZnPc3a at 1H-NMR spectrum was occured between δ 8,31-7,36. In the UV-Vis absorption spectrum of ZnPc3a and Mn(Cl)Pc3b, 363, 330 nm (B band) and 703, 655 (750) nm ( Q band) were observed in THF solution respectively. Also in the mass spectra of Mn(Cl)Pc3b, the [M-Cl+1]+ peak was seen at m/z: 2096,40 verified the formation of phthalocyanine. The electrochemical and spectroelectroelectrochemical properties of synthesized phenylthiazole substituted phthalocyanines were investigated. Electrochemical and spectroelectrochemical results of the peripheral tetrasubstituted phthalocyanines showed that Co(II) and Mn(II) metal centres in the core of the CoPc1a and Mn(Cl)Pc1c gave extra metal based redox processes in addition to the Pc based electron transfer reactions. Also The thiazole substituent achieved the electropolymerisation of the complexes. MnPc (Mn(Cl)Pc1c) based modified electrode shows considerably high electrocatalytic activity for OER. During reduction reactions of non peripheral tetrasubstituted phthalocyanines, ZnPc2b showed three ring based processes and CoPc2a and Mn(Cl)Pc2c illustrated metal ion electron transfer reactions in addition to the Pc based reactions. Due to the different metal center, each complex illustrate different electrochemical responses. Especially CoPc2a and Mn(Cl)Pc2c have rich redox properties due to the electron transfer reactions of the central metals.
Thiazole substituted phthalocyanines
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Thesis (Ph.D.) -- Istanbul Technical University, Institute of Science and Technology, 2019
Keywords: Ftalosiyaninler; Tiyazoller; Phthalocyanines; Thiazoles